KARAKTERISTIK PENGUSAHA PERIKANAN IKAN JULUNG ASAP DI DESA SULUBOMBONG, SULAWESI TENGAH-INDONESIA - Sambagu, Cecilia; Manuhutu, Elia A.; Kaunang, Stella T. (Institute of Computer Science (IOCS), 2024)
The village of Sulubombong, Central Sulawesi, is renowned for its smoked Julung fish production. Entrepreneurship is a prevalent occupation in this area. The characteristics and spirit of entrepreneurship are essential for achieving desired goals, namely profitability and sustainable business operations. This research aims to determine the characteristics of Julung fish entrepreneurs in Sulubombong Village, with a total of 5 respondents. The study employs 6 variables: self-confidence, task, and results orientation, risk-taking, leadership, originality, and future orientation. The findings reveal that entrepreneurs in Sulubombong Village possess all six characteristics studied, namely leadership, future orientation, originality, risk-taking, self-confidence, and task and results orientation.